STRATEGI PENINGKATAN PRODUKSI SENYAWA ARTEMISININ DAN TURUNANNYA DENGAN KONSEP BIOTEKNOLOGI - khasanah, uswatun - (Pharmaceutical Journal of Indonesia, 2019)
Artemisinin is a sesquiterpen lactone that was isolated from the Artemisia annua. Artemisinin was used as antimalarial since 1980, when chloroquine resistance case occurred. The demand of artemisinin as antiamalarial was not accompanied by an increase in artemisinin production. Until now, artemisinin production is obtained through isolation process of genus Artemisia. Various studies have been carried out to meet the needs of artemisinin as antimalarial drug. Some studies used biotechnology technic for example plant tissue culture, genetic engineering to modulate artemisinin biosynthetic pathway, and the addition of organic fertilizer in A.annua agriculture. Some researches added compounds which play a role Â in the biosynthesis of artemisinin in A.annua cell culture, e.g mevalonic acid, sodium acetate and casein. In addition, the production of artemisinin derivatives is also carried out through biotechnology techniques using hair root culture from certain plants. Production of artemisinin is also increased by adding organic fertilizers, such as NaCl, potassium phosphate, and ammonium nitrate. Several studies also produce transgenic plants by inserting genes that encode terpenoid precursor compounds, farnesil pyrophosphate.